Developing an Early Warning System for BOP and Financial Crises: The Case of the Philippines - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1998)
After the onset of the East Asian financial crisis, the interest in early warning system has been revived. While there are different causes to which crises can be attributed, early warning system can be utilized to predict its emergence via monitoring of key economic variables. Thus, policymakers are granted sufficient time to implement policy measures meant to minimize the adverse impacts of the crisis, if not to completely curb it. Although there are other methods to identify possible indicators, like the probability approach, the EWS developed by Kaminsky and Reinhart, is used in this paper because of various issues the probability approach are not capable of addressing. The concept of EWS is then applied to the Philippines. The study has identified two episodes of currency crises: October 1983 and September 1997. However, the computation of time-series probabilities is slightly modified. Results lend validity to the hypothesis of self-fulfilling crisis.
Keywords: 330; early warning system; self-fulfilling crisis